Stress/recovery balance during the Girobio: profile of highly trained road cyclists - Filho, E.; Di Fronso, S.; Forzini, F.; Agostini, T.; Bortoli, L.; Robazza, C.; Bertollo, M. (Sport Sciences for Health, 2013)
The purposes of this study were to (a) determine and compare the magnitude of pre-post recovery and stress scores among highly trained cyclists participating in the "Girobio", and (b) identify stress/recovery balance factors that remained constant from pre- to post-race testing. Sixty-seven cyclists with extensive international experience and representing various teams participated in the study. Data were collected during the Girobio-2012, a multi-stage competition for Under 23 and Elite cycling categories, held annually in Italy. Participants responded to the Recovery-Stress Questionnaire for Sport 1 day before the first stage (test, T1) and on the day of the ninth/final stage (i.e., 5 h prior to the start) (retest, T2). Compared to test scores, at retest we expected to find higher stress and lower recovery values for all subscales with the exception of self-efficacy and self-regulation, which reflect goal-oriented experiences rather than psychophysical states linked to a given race. Overall, results were in this expected direction. No significant effects were found for one general stress subscale (i.e., Conflict/Pressure), two general recovery subscales (i.e., Success and Social Recovery), and two sport-specific recovery subscales (i.e., Personal Accomplishment, and Self-Efficacy), thus suggesting the stability of these stress/recovery factors over time. Collectively, these findings reinforce the importance of assessing multiple indicators of stress/recovery balance to establish mental training guidelines aimed at addressing and preventing both temporary and relatively chronic maladaptation among cyclists.